Developed embedded switched‐Z‐source inverter. Issue 9 (1st July 2016) - Babaei, Ebrahim; Shokati Asl, Elias; Hasan Babayi, Mohsen; Laali, Sara
Abstract : In this study, a new topology for switched Z‐source inverter is proposed. This inverter in comparison with the conventional Z‐source inverter needs higher number of active elements, lower number of capacitors and inductors. Reduction of weight, size and cost are the main advantages of the proposed topology. In addition, this inverter is able to solve the problem of short circuit across the inverter leg and consists of higher value of voltage gain when compared with the conventional switched boost inverter. Moreover, the developed topology of the proposed inverter based on switched‐inductor cells is introduced. The performance of the proposed inverter in different operating modes is investigated. The proposed topologies are also compared with the conventional Z‐source inverters from different points of view such as number of elements, the voltage gain and capability of tolerate the inverter short circuit. Finally, the accuracy performance of the proposed inverter is reconfirmed by using the simulation results in EMTDC/PSCAD software and also experimental results.